2015
DOI: 10.1007/s00428-015-1733-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial microsatellite instability in patients with metastatic colorectal cancer

Abstract: Mitochondrial microsatellite instability (mtMSI), a change in length in mtDNA microsatellite sequences between normal and tumor tissue, has been described as a frequent occurrence in colorectal cancer (CRC). We evaluated the prevalence and prognostic value of mtMSI and its relation to nuclear microsatellite instability (MSI) in patients with metastatic CRC (mCRC). At six loci (D310, D514, D16184, ND1, ND5, and COX1), the mitochondrial DNA sequence was analyzed in normal and tumor tissue, and the mtMSI status w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
(99 reference statements)
1
17
0
Order By: Relevance
“…Less data are available for metastatic CRC. The detection rate of mitochondrial instability for the LN of this study was in accordance with a recent publication on metastatic CRC 23 considering all three investigated loci (54.4%) or D16184 only (1.6%), negligibly lower than reported by these authors for D310 only (50.5%) and little higher than reported in the case of D514 only (4.9%). In contrast, the rate of mtMSI in DM of our patient cohort was less than half of that reported by others.…”
Section: Discussionsupporting
confidence: 92%
“…Less data are available for metastatic CRC. The detection rate of mitochondrial instability for the LN of this study was in accordance with a recent publication on metastatic CRC 23 considering all three investigated loci (54.4%) or D16184 only (1.6%), negligibly lower than reported by these authors for D310 only (50.5%) and little higher than reported in the case of D514 only (4.9%). In contrast, the rate of mtMSI in DM of our patient cohort was less than half of that reported by others.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding mtDNA, microsatellite instability (mainly in D310 region) was found in 40% of colorectal cancer patients analyzed here. Nevertheless, the occurrence of such mutations may not have the same molecular background as the nuclear ones, as previous studies have shown lack of any association between the occurrence of mitochondrial and nuclear microsatellite instability (Venderbosch et al., ). It was previously proposed that polymerase gamma may be involved in mitochondrial length variation in D310 sequence in cancer (Skonieczna et al., ), but such associations were not observed for colorectal cancer patients (Linkowska et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, no association has been identified between mtDNA mutations and mtMSI status, and no mtMSI-positive GC cases have exhibited large deletions in mtDNA (44). Furthermore, mtMSI appears to be particularly frequent at the D310 locus; however, the high prevalence of mtMSI was not associated with the prognosis of patients with CRC (23,47). Notably, a previous study reported that stromal mtMSI may have possibly served an independent role in the pathogenesis of CC (48).…”
Section: Gastric Cancer Colon Cancer Rectum Cancermentioning
confidence: 83%
“…Mitochondrial MSI (mtMSI) in GIC. mtMSI has been reported to frequently occur in GC and CRC (23,24). In the present study, the mtMSI in 69 Chinese patients with GIC were analyzed.…”
Section: Homoplasmic Mutations Of the Mtdna D-loop In Gicmentioning
confidence: 95%